2013
DOI: 10.1017/s1366728912000788
|View full text |Cite
|
Sign up to set email alerts
|

Language proficiency and executive control in bilingual children

Abstract: The relation between language proficiency and executive functions has been established for monolingual children. The present study addresses this issue in bilingual children, comparing the language proficiency of sequential English–Hebrew bilingual preschool children as determined by standardized assessment instruments and generic executive control in inhibition, sorting and shifting tasks. Participants were recruited from regular and language preschools and classified according to their language proficiency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
48
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 62 publications
8
48
1
Order By: Relevance
“…For interference suppression, however, a significant difference between the bilingual SLI group and the bilingual typically developing group emerged. This result is consistent with a previous study on bilingual children with low language proficiency who demonstrated deficits on an embedded figure task involving misleading contexts (Iluz‐Cohen and Armon‐Lotem ). Importantly, a significant difference on interference suppression did not emerge when the bilingual SLI group was compared with the monolingual typically developing group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For interference suppression, however, a significant difference between the bilingual SLI group and the bilingual typically developing group emerged. This result is consistent with a previous study on bilingual children with low language proficiency who demonstrated deficits on an embedded figure task involving misleading contexts (Iluz‐Cohen and Armon‐Lotem ). Importantly, a significant difference on interference suppression did not emerge when the bilingual SLI group was compared with the monolingual typically developing group.…”
Section: Discussionsupporting
confidence: 92%
“…Published studies on bilingual children with SLI are extremely rare and, so far, focused almost exclusively on morphosyntactic development (see Paradis , for a review). To our knowledge, only one study has explored executive functioning in bilingual children with low language proficiency (Iluz‐Cohen and Armon‐Lotem ). This study included 10 sequential bilingual English−Hebrew speaking children that were designated as ‘low language proficiency’ group (not SLI) by the authors.…”
Section: Introductionmentioning
confidence: 99%
“…Bedore et al, 2012 on assessing language dominance). Several aspects known to vary in bilingual experience have been argued to have an effect on executive function performance, such as proficiency (Gutiérrez-Clellen, Calderón, & Ellis Weismer, 2004;Iluz-Cohen & Armon-Lotem, 2013;Rosselli, Ardila, Lalwani, & Vélez-Uribe, 2015), language dominance (Mueller Gathercole et al, 2014;Weber, Johnson, Riccio, & Liew, 2015), language exposure (Brito, Sebastián-Gallés, & Barr, 2015), and patterns of language switching (de Bruin et al, 2015;Verreyt, Woumans, Vandelanotte, Szmalec, & Duyck, 2015;Scaltritti, Peressotti, & Miozzo, 2015;Soveri, Rodriguez-Fornells, & Laine, 2011). A number of researchers are now calling for the integration of the variability of bilingual experience in the analyses (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…language proficiency, age of second language acquisition, etc.) have found that they are related to cognitive control functioning (Iluz-Cohen & Armon-Lotem, 2013; Luk, DeSa, & Bialystok, 2011; Prior & Gollan, 2011). In our case, the bilinguals we test, generally, come from immigrant homes where Spanish is primarily spoken.…”
Section: Introductionmentioning
confidence: 99%